Modalities In “Pidato Kenegaraan Presiden Joko Widodo Tahun 2023 Dalam Rangka Hut Ke-78 Republik Indonesia”: Systemic Functional Linguistics Perspective - I Gede Madriana; I Ketut Suardana (Journal of Pragmatics Research, 2025)
This research investigated the functions of modality applied in the text of “Pidato Kenegaraan Presiden Joko Widodo Tahun 2023 Dalam rangka HUT ke-78 Republik Indonesia”. The research used qualitative research, grounded theory. The data source was taken from Kompas.com. From the clauses used in the text. The research technique used to identify the data was Teknik Pilah Unsur Penentu by classifying each of the clause elements. Adjuncts, verbs, auxiliary modalities, and clauses were identified to find out the functions of modality. The theory used to analyze the data was the theory of language as interpersonal, especially modality, proposed by Halliday. The research results suggested that this research found modalization and modalization in the text. Modaliization involves a Proposition, namely: (i) Low fact propositional modality is used by Jokowi’s political opponents to spread fake information. (ii) High fact propositional modality is used by Jokowi to clarify the bad issue addressed to Jokowi. Whereas, modulization involves proposal modalities which are used by Jokowi to invite all of the communities to be involved in ongoing and further development. In addition, proposal modalities are used in Jokowi’s expectation for further development. Academically, this research result brings some advantages for linguistics research, such as semiotics, language philosophy, and discourse analysis. Therefore, this research is expected to be able to stimulate other linguistic researchers to explore other politicians’ character regarding to political speech from modality perspective.